Ochrona dziedzictwa kultury w systemie prawnym Unii Europejskiej - Sobczak, Witold (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
For a long time the European Community, followed by the European Union, did not pay considerable attention to the protection of European cultural heritage or to the issue of cultural policy, and they left this field, more or less consciously, to the system of the Council of Europe. The matters concerning this field were only stipulated in Art. 151 of the Treaty establishing the European Community. However, this article limits the activity of the European Union in the realm of culture to supplementary and supportive activities. When undertaking such activities, it is necessary to respect national and regional diversity and to bring the common cultural heritage of Europe to the fore. Cultural policy shall remain the domain of the Member States, though. The Union should encourage cooperation between Member States and supplement their activities as stipulated in Art. 151. The realm of culture in Community law is only regulated by so-called soft law. The Community legislative acts in the form of regulations, directives or decisions touch upon this field only when the realm of culture overlaps with the realms regulated by Community laws, such as the transfer of persons, goods, commodities and the protection of competition.